A baseline classification of riparian woodland plant communities in the Okavango Delta, Botswana. Issue 2 (2nd April 2016) - Tsheboeng, Gaolathe; Murray-Hudson, Mike; Kashe, Keotshepile
Abstract : In the Okavango Delta information on the riparian woodland vegetation community composition and distribution is generally lacking. Past studies in the Delta were mainly focused on the quantitative classification of seasonal floodplain herbaceous vegetation communities. The aim of this study was to determine riparian woodland vegetation communities in the Okavango Delta. Vegetation sampling was conducted in 20 m × 50 m randomly placed plots. The plots were placed along a gradient from the main water body to the drier fringe of the riparian zone. Plant species present in each plot were recorded with their estimated percentage cover using the Braun–Blanquet cover abundance scale. Hierarchical cluster analysis was used to determine vegetation communities. Indicator species analysis was used to calculate indicator values for species groups defined from the cluster analysis. Plant species and diversity were determined for each vegetation cluster. Multi-response permutation procedures (MRPP) were used to determine significance of differences between communities. The Kruskal–Wallis test was used to compare species diversity and richness between vegetation communities. Four vegetation communities were identified: Croton megalobotrys– Hyphaene petersiana, Vachellia erioloba–Diospyros lycioides, Syzygium cordatum–Phoenix reclinata and Garcinia livingstonei–Senegalia nigrescens. In this classification, the Syzygium cordatum–Phoenix reclinata and Garcinia livingstonei–Senegalia nigrescens plant communities are found in frequently flooded regions, whereas the Croton megalobotrys–Hyphaene petersiana and Vachellia erioloba–Diospyros lycioides are in occasionally flooded regions. Total number of species was highest in the Garcinia livingstonei–Senegalia nigrescens and lowest in the Syzygium cordatum–Phoenix reclinata vegetation communities. The MRPP showed that there was significant ( p < 0.05) differences between vegetation communities. Species diversity and richness were significantly ( p < 0.05) higher in the Garcinia livingstonei–Senegalia nigrescens vegetation community. This study provided an inventory of riparian woodland plant communities, which can be used as a vital monitoring tool of vegetation change in the Okavango Delta.